(3fhQ GdYjhf aj JdNjU SjQ GdCejf GdeCehfs - (3GHf SjO GdfGS GdjYeQj , aJM GdOjf eMeO Hf eMeO, aJM GdOjf CHh GdaJM,J (B734 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aGJM CHhGH GdfOi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B63 (3b (B- (3U(B104 (3bs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B280 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1183s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs